PENGARUH TERAPI PIJAT SWEDIA TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN LANSIA DENGAN HIPERTENSI DI BALAI SOSIAL LANJUT USIA “MANDALIKA” NTB - Rabiatul Adawiyah (STIKES Mataram, 2017)
The older the age is, it can cause the degrading of some physical or psychological functions experienced by people as the effect of aging process. It also includes triggering health problems in the elderly people. One of the degenerative disease that is mostly experienced by the elders is hypertension which is a chronic disease caused by the lacking of blood vessel’s wall elasticity as the effect of aging process. The Swedish massage therapy is one of complementary therapy which is believed to be effective in giving the relaxation responses and also to reduce the blood pressure. Then, it brought to a reseearch where it was aimed to examine the effect of Swedish massage therapy to the changes of blood pressure in elderly people “Mandalika” NTB. This research was using one group pre-post test design with 20 elderly people with hypertension as samples which were selected by purposive sampling method. Data analyzing used was paired t-test with 0,05 (5%) signifance level. Based on the statistical test, t-count is 8,048 and was compared with t-table on d.b =19, it had result on t-table 2,093.Thus, t-count > t-tablemeant that there was an effect of Swedish massage therapy to the change of blood pressure in elderly patients with hypertension. Based on this reseach,itcould be concluded that there was an effect of Swedish massage therapy to the changes of blood pressure in elderly patients with hypertension. Therefore, the Swedish massage could be used as an alternative care to help in reducing blood pressure especially to the elderly people with hypertension. Keywords: Elderly people;Hypertension; Swedish massage